P3 Sleep characteristics and quality of life in patients with fibrotic interstitial lung disease. (12th November 2019) - Myall, KJ; Roque, D; Simpson, S; Suh, ES; West, A; Kent, B
Abstract : Introduction and objectives: Both nocturnal hypoxaemia (NH) and obstructive sleep apnoea (OSA) are common in patients with interstitial lung disease. We aimed to prospectively measure the incidence of sleep disordered breathing in these patients, and assess their relationship with disease specific and respiratory quality of life measures. Methods: Prospective observational study of patients with an MDT diagnosis of a fibrotic interstitial lung disease who all underwent a home sleep study. Data was collected for demographic and clinical characteristics, pulmonary function testing, six-minute walk test (6MWT), and patient-reported disease-specific quality of life using the King's Brief Interstitial Lung Disease questionnaire (KBILD) and the St George's Respiratory Questionnaire (SGRQ). Results: 29 patients were included. Nine (31.0%) had nocturnal hypoxaemia (defined by ≥10% of sleep with SpO2 ≤90%), and 10 (34.4%) had at least moderately severe OSA (ODI ≥15). Both NH and OSA were associated with a trend towards a reduction in quality of life. In patients with NH, median KBILD score was 56.67 vs 53.80 in patients without (p=0.15). Mean SGRQ was 50.03±14.32 in patients with NH and 34.55±19.38 in patients without (p=0.09). In patients with at least moderately severe OSA, median total KBILD score was 59.52 vs 56.51 in patients without (p=0.49). Mean SGRQ in patients with OSA was 47.20±21.44 vs 33.92±16.39 in unaffected patients (p=0.13). Patients with OSA had a significantly lower FVC than those without (Mean 2.37±0.64 Vs 2.88±0.58, p=0.04. Mean BMI was 31.36±7.84 in patients with NH compared with 29.56±4.68 in those without (p=0.45), and in patients with OSA mean BMI was 32.62±6.84 vs 28.80±4.78 in those without (p=0.09). Conclusions: NH and OSA are common in patients with fibrotic interstitial lung disease, and, both tend towards a reduction in quality of life as measured by SGRQ and KBILD. Baseline FVC is lower in patients with OSA, although not NH, and as expected patients with OSA were more obese than those without.